Exploring the effect of cold stress on the semen quality parameters of buffalo bulls - Karpenahalli Ranganatha Sriranga; Pawan Singh; Ravinder Singh; Tejeshwari Satpute; Prince Vivek; Tushar Kumar Mohanty; Pradeep Kumar; Ranjit Singh Kataria; Megha Pande; Manishi Mukesh (Revista Científica)
The objective of the current study was to evaluate how buffalo bulls’ semen quality is affected by cold stress. A total of 26 adult Murrah buffaloes were taken at the Artificial Breeding Research Centre, ICAR-National Dairy Research Institute, Karnal, India. Semen collection of these bulls was done twice during the peak of winter and spring seasons with overall average ambient temperature (°C) of 12.55±0.22 and 20.21±0.68, respectively, and blood was collected on the same day for biochemical analysis. Routine seminal attributes, viz., semen volume, sperm concentration, mass activity, individual motility, viability, acrosome integrity, and hypo-osmotic swelling test (HOST), were evaluated immediately after semen collection, and diluted semen was cryopreserved for further studies. Additionally, fresh and frozen sperm were subjected to flow cytometric analysis utilizing the Luminex MUSE Cell Analyzer and CytoFLEX, Beckman Coulter-Life Sciences, respectively. Sperm motility characteristics were assessed using a CASA (Hamilton Thorne IVOS II) with the help of eight chambered Leja slides. Further, serum hormones were assayed through the CMIA technique, and the antioxidant status of both serum and seminal plasma was done using standard protocol. Statistical analyses were performed using IBM SPSS Statistics software (v.20.0). The THI during the winter and spring seasons was 54.85±0.38 (THI range; 40.93 – 60.38) and 66.89±1.03 (THI range; 60.04 – 77.99), respectively, while the cold stress index was 857.62±8.89 and 793.08±14.10, respectively, demonstrating that the values varied significantly between the seasons (p=0.001). Fresh seminal attributes such as volume (2.86±0.20 vs. 2.73±0.15 ml, p=0.616), concentration (1181.94±71.32 vs. 1115.10±78.34 x 106/ml, p=0.529), mass activity (2.28±0.09 vs. 2.47±0.08, p=0.094), viability (81.95±1.07 vs. 82.13±0.89%, p=0.896), and acrosome integrity (86.17±0.86 vs. 87.53±0.75%, p=0.239), did not vary between the extreme winter and comfortable spring seasons. However, individual motility, HOST (66.75±1.41 vs. 71.13±1.25%, p=0.022), and discard rate (48.36±1.92 vs 36.44±5.51%, p=0.024) of semen were affected by cold stress. ROS (+) cells and apoptotic cells in fresh semen were not affected by cold stress, despite their higher values in the winter season. A similar trend was observed with MitoSOX (+) cells and live acrosome intact cells in frozen semen. Further, cold stress had a significant influence on the sperm kinematic characteristics of both fresh and frozen-thawed semen. Serum hormones such as Triiodothyronine (5.23±0.16 vs. 4.41±0.14 ng/mL, p=0.000), testosterone (0.99±0.12 vs. 1.68±0.17 ng/mL, p=0.002), cortisol (3.66±0.43 vs 2.29±0.12 ng/mL, p=0.004), and LDH (1078.54±12.32 vs 988.23±13.54 U/L, p=0.000) were affected by the cold weather. In addition, GSH and MDA concentrations in both seminal plasma and serum were affected by cold stress. In conclusion, frigid temperatures also contribute as a stress factor, further leading to a significant reduction in the semen quality of buffalo bulls.